COLONIAL RELOCATIONS IN NORTHERN NAMIBIA: FROM THE RIVER SIDE VILLAGE TO NKARAPAMWE BLACK TOWNSHIP IN RUNDU - Kletus Muhena Likuwa (European Scientific Journal, ESJ, 2014)
Using oral interviews, archival documents and a review of literature, this paper explores the 1960s colonial relocation of black people in Namibia from the Kavango River villages to Nkarapamwe Black Township in Rundu. The paper considers the relevance of the political situation in Namibia at that time, specifically the political insecurity situation along the Kavango River as part of the factors that led to the relocation. The aim is to analyze why people refused to move to the township and what strategies the colonial state used to achieve its objectives of relocation and how the relocation impacted on the economic and social aspects of the community. In the case of the riverside villages in Rundu, the motives for relocation were political in nature to monitor the ongoing frontal war by SWAPO along the Kavango River and although the authorities gave other benign reasons for relocation people hardly found them convincing and discerned their own reasons for being relocated. People initially refused to be relocated because they believed and feared rightly so that the houses in the new township were too small for their family and cultural practices and that they would have no ownership of the house and they would be compelled to pay for all costs of developments in the new black township. While some people moved voluntarily to Nkarapamwe Township in 1968 there are indications that the relocation was a force to many who had initially refused to move but were eventually forced to do so by the threat of having their homesteads burned and losing their jobs. The naming of their community by a proverbial name Nkarapamwe asserted the residents’ desire to work closely together to avoid bringing each other into trouble or disrepute with the township administration officials. The paper asserts that relocation impacted negatively on people’s economic aspects as it meant finding ways to recover costs of their loss of properties. Equally, it impacted on the people’s social aspects as old interpersonal relations and social structure were irretrievably destroyed. This case study is significant as it provide an example of colonial relocation which can be a lesson to the post-colonial township authorities in Namibia on how relocation impacts on people and why authorities should become more considerate of community plights before, during and after relocation process.